The hanging girl eaudiobook - Adler-Olsen, Jussi (Department Q, 2015)
New York Times  and internationally bestselling author Jussi Adler-Olsen delivers an exhilarating mystery in the Department Q series, featuring Detective Carl Mørck and his enigmatic assistants, Assad and Rose.   In the middle of his usual hard-won morning nap in the basement of police headquarters, Carl Mørck, head of Department Q, receives a call from a colleague working on the Danish island of Bornholm. Carl is dismissive when he realizes that a new case is being foisted on him, but a few hours later, he receives some shocking news that leaves his headstrong assistant Rose more furious than usual. Carl has no choice but to lead Department Q into the tragic cold case of a vivacious seventeen-year-old girl who vanished from school, only to be found dead hanging high up in a tree. The investigation will take them from the remote island of Bornholm to a strange sun-worshipping cult, where Carl, Assad, Rose, and newcomer Gordon attempt to stop a string of new murders and a skilled manipulator who refuses to let anything—or anyone—get in the way.